On the recognition and taxonomic position of Quercus mongolicoides (Fagaceae) - Hiroki, Shōzō (Phytotaxa, 2024)
In Japan, a new clade of Quercus Linnaeus (1753: 994) has been recently recognized, and its taxonomic position is under discussion. The present paper briefly reviews the history of the change of its scientific name and discusses its taxonomic position.